2021
DOI: 10.1016/j.jtct.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of SARS-CoV2 Emergency-Use Authorized Vaccines for Allogeneic Hematopoietic Stem Cell Transplant Recipients

Abstract: Background : The safety and efficacy of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) emergency-use authorized (EUA) vaccines has been confirmed in general population. However, there is no data on its safety/tolerability or efficacy in recipients of allogeneic hematopoietic stem cell transplant (HCT). Objectives : We performed this study to identify the incidence of adverse events following SARS-CoV2 EUA vaccines and the incidence of new onset GVHD or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 17 publications
8
70
1
Order By: Relevance
“…According to Centers for Disease Control and Prevention (CDC) data the percentages of people affected by side effects after the first and the second vaccine dose were, respectively: redness 4.5% and 7.25%; swelling 5.8% and 7.5%; pain 83.1% and 66,1%; fever 3.7% and 15.8%; fatigue 47.4% and 59.4%; headache 41.9% and 51.7%; chills 14.0% and 35.1%; muscle pain 21.3% and 37.3%; joint pain 11% and 21.9% [ 9 ]. The comparison of our study results with this data may suggest that young adults after bone marrow transplantation tolerate mRNA COVID-19 vaccine no worse than the general population, which was also seen by other authors [ 10 ]. However, this comparison should be taken with caution considering significantly smaller number of patients involved in this study in comparison with reports describing general population.…”
Section: Discussionsupporting
confidence: 89%
“…According to Centers for Disease Control and Prevention (CDC) data the percentages of people affected by side effects after the first and the second vaccine dose were, respectively: redness 4.5% and 7.25%; swelling 5.8% and 7.5%; pain 83.1% and 66,1%; fever 3.7% and 15.8%; fatigue 47.4% and 59.4%; headache 41.9% and 51.7%; chills 14.0% and 35.1%; muscle pain 21.3% and 37.3%; joint pain 11% and 21.9% [ 9 ]. The comparison of our study results with this data may suggest that young adults after bone marrow transplantation tolerate mRNA COVID-19 vaccine no worse than the general population, which was also seen by other authors [ 10 ]. However, this comparison should be taken with caution considering significantly smaller number of patients involved in this study in comparison with reports describing general population.…”
Section: Discussionsupporting
confidence: 89%
“…Another study demonstrated a similar spectrum of adverse effects and concluded that mRNA SARS-CoV-2 vaccines appear to be relatively safe after allogeneic HCT. 4 The findings of these first observational reports are consistent with expected vaccine responses in allogeneic HCT recipients based on studies using other vaccines. Guidelines generally recommend administering routine nonlive vaccines at least 6 months after HCT given the pattern of immune reconstitution and relatively poor response rates (<50%) at earlier time points, although earlier vaccination can be considered for pathogens such as influenza in the context of community outbreaks.…”
supporting
confidence: 75%
“…Similarly, Ali et al. reported recently in a retrospective study that 9.7% of HSCT patients developed new chronic GvHD and 3.5% experienced worsened chronic GvHD after vaccination with mRNA vaccines [29] . Moreover, Ram et al.…”
Section: Discussionmentioning
confidence: 67%